Development of E-Module Based Geography Teaching Materials - Rezki Pratama; Yurni Suasti; Ernawati Ernawati (Postgraduate School, Universitas Negeri Padang, 2020)
This study aims to know the effectiveness of the use of e-module-based geography teaching materials with inserts of religious values. This type of research is development research (Research and Development) by adapting the ADDIE model. Validation of teaching materials is obtained from learning material experts, learning media experts, and learning design experts. The practicality of teaching materials is obtained from teachers and students. The effectiveness of teaching materials is obtained from student learning outcomes. The results showed that: 1) The quality of e-module-based geography teaching materials is very valid and very practical. The validity assessment from the learning material expert got the final score of 92.5%, the learning media expert got the final score of 91.25%, and the learning design expert got the final score of 85.71%. The practicality assessment got a final score of 88.33%; 2) Student learning outcomes data showed that there was a change in scores from pre-test to post-test with an average N-gain score of the experimental class of 77.07 belonging to the high category. Meanwhile, the average N-gain score for the control class is 60.05, which is included in the medium category. Based on the results of the t-test, it can be concluded that the significance value (2-tailed) is 0.000 so the significance value (2-tailed) of 0.000 < the significance value of 0.05. This means that there is a difference between experimental classes that are given special behaviors using module-based teaching materials and getting higher scores than control classes that do not use e-module-based teaching materials. So it can be concluded that the teaching materials developed can increase the effectiveness of learning.